2012
DOI: 10.1038/cdd.2012.46
|View full text |Cite
|
Sign up to set email alerts
|

Calpains mediate epithelial-cell death during mammary gland involution: mitochondria and lysosomal destabilization

Abstract: Our aim was to elucidate the physiological role of calpains (CAPN) in mammary gland involution. Both CAPN-1 and -2 were induced after weaning and its activity increased in isolated mitochondria and lysosomes. CAPN activation within the mitochondria could trigger the release of cytochrome c and other pro-apoptotic factors, whereas in lysosomes it might be essential for tissue remodeling by releasing cathepsins into the cytosol. Immunohistochemical analysis localized CAPNs mainly at the luminal side of alveoli. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 40 publications
(60 reference statements)
1
67
0
Order By: Relevance
“…14 Although the molecular events that underlie LMP in the mammary gland remain unclear, the activation of Stat3 and calpain appears to have a prominent role. 14,39 Interestingly, Stat3 transcription is also upregulated and its phosphorylation increased in the rd10 retina at P20, 40 the time point at which we observed LMP in the present study. Moreover, this transcription factor is essential to determine photoreceptor cell fate during retinal development 41 and its cleavage has been linked to calpain activation.…”
Section: Discussionsupporting
confidence: 63%
“…14 Although the molecular events that underlie LMP in the mammary gland remain unclear, the activation of Stat3 and calpain appears to have a prominent role. 14,39 Interestingly, Stat3 transcription is also upregulated and its phosphorylation increased in the rd10 retina at P20, 40 the time point at which we observed LMP in the present study. Moreover, this transcription factor is essential to determine photoreceptor cell fate during retinal development 41 and its cleavage has been linked to calpain activation.…”
Section: Discussionsupporting
confidence: 63%
“…Alternatively, Arnandis et al . (2012) [41] has shown that calpains are responsible for mitochondrial and lysosomal membrane permeabilization during lysosomal-mediated mammary epithelial cell death in mice. Also, milk yield is known to decline as function of many factors after peak lactation, including decrease in alveolar secretory epithelial cell number due to programmed cell death [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, calpains are involved not only in necrosis but also in apoptotic cell death, in which they were shown to process BID into proapoptotic t-BID (Gil-Parrado et al 2002). Moreover, calpains were suggested to translocate to the lysosomal membrane of epithelial cells during mammary gland involution to cleave cytosolic parts of membrane proteins, such as LAMP-2, contributing to LMP and thus triggering apoptotic cell death (Arnandis et al 2012). In addition, it was shown that LMP in mammary epithelium is Stat3-dependent and independent of the executioner caspases caspase-3, -6, and -7.…”
Section: Lysosomes In Apoptosismentioning
confidence: 99%